LINC00452 overexpression reverses oxLDL-induced injury of human umbilical vein endothelial cells (HUVECs) via regulating miR-194-5p/IGF1R axis - Yuan, Liang; Wang, Dajie; Zhou, Zhaofeng (Frontiers in Cardiovascular Medicine, 2022)
It has been reported that atherosclerosis (AS) is the basis of the development of coronary artery disease (CAD). In addition, a previous study demonstrated that long non-coding RNA LINC00452 was notably downregulated in the whole blood of patients with CAD. However, the role of LINC00452 in the progression of AS remains unclear. Therefore, to mimic AS in vitro, HUVECs were treated with 100 μg/ml oxLDL for 24 h. Reverse transcription-quantitative PCR was performed to detect the expression levels of LINC00452 and IGF1R in HUVECs. Additionally, the cell angiogenetic ability was assessed by tube formation assay, while dual-luciferase reporter assay was carried out to explore the association among LINC00452, miR-194-5p, and IGF1R. The results showed that LINC00452 was downregulated in oxLDL-treated HUVECs. In addition, HUVEC treatment with oxLDL significantly inhibited cell viability, proliferation, and angiogenesis. However, the above effects were all reversed by LINC00452 overexpression. Furthermore, LINC00452 overexpression in HUVECs remarkably inhibited oxLDL-induced cell apoptosis and endothelial to mesenchymal transition. In addition, LINC00452 overexpression could markedly reverse oxLDL-induced inhibition of angiogenesis in HUVEC. The results of dual-luciferase reporter assay indicated that LINC00452 could bind with miR-194-5p. In addition, IGF1R was identified as a downstream target of miR-194-5p. And LINC00452 was able to regulate the miR-194-5p/IGF1R axis in HUVECs. Moreover, LINC00452 overexpression obviously reversed oxLDL-mediated growth inhibition of HUVEC via regulating the miR-194-5p/IGF1R axis. Overall, the current study demonstrated that LINC00452 overexpression reversed oxLDL-induced growth inhibition of HUVECs via regulating the miR-194-5p/IGF1R axis, thus providing a potential beneficial targets for AS.